GsMTx-4 combined with exercise improves skeletal muscle structure and motor function in rats with spinal cord injury - Xin Zhang; Xinyu Liu; Qianxi Li; Chenyu Li; Xinyan Li; Jinghua Qian; Jianjun Li; Xuemei Li (PLoS ONE, 2025)
Motor dysfunction and muscle atrophy are typical symptoms of patients with spinal cord injury (SCI). Exercise training is a conventional physical therapy after SCI, but exercise intervention alone may have limited efficacy in reducing secondary injury and promoting nerve regeneration and functional remodeling. Our previous research found that intramedullary pressure after SCI is one of the key factors affecting functional prognosis. It has been reported that GsMTx-4, a specific blocker of the mechanosensitive ion channels Piezo1, can protect the integrity of the neuromuscular junction and promote nerve regeneration, and thus has the potential as a therapeutic agent for SCI. In this study, we observed the combined and separate therapeutic effect of GsMTx-4 and exercise on the structure of the soleus muscle and motor function in rats with SCI. At 42 days post-injury, compared with SCI rats, the Basso–Beattie–Bresnahan score (P = 0.0007) and Gait Symmetry (P = 0.0002) were significantly improved after combination therapy. On histology of rat soleus muscle, compared with SCI rats, the combined treatment significantly increased the wet weight ratio, muscle fiber cross-sectional area and acetylcholinesterase (all P<0.0001). On histology of rat spinal tissue, compared with SCI rats, the combined treatment significantly increased neuron counts and BDNF levels, and significantly reduced the percentage of TUNEL-positive cells (all P<0.0001). On physiology of rat soleus muscle, compared with SCI rats, the combined treatment increased the succinate dehydrogenase expression (P<0.0001), while the expression of α-glycerophosphate dehydrogenase (P<0.0001) and GDF8 protein (P = 0.0008) decreased. Results indicate the combination therapy effectively improves histopathology of spinal cord and soleus muscle in SCI rats, enhancing motor function. This study was conducted on animal models, it offers insights for SCI treatment, advancing understanding of lower limb muscle pathology post-SCI. Further research is needed for clinical validation in the future.